The impact of extracorporeal shock wave therapy on pain, grip strength and functionality in patients with medial epicondylitis and lateral epicondylitis - Karakoyun, Ahmet; Calik, Yalkin (Annals of Medical Research, 2022)
Aim: The aim of this study was to evaluate the effectiveness of extracorporeal shock wave therapy (ESWT) and conventional physical therapy applications on pain, grip strength and functionality in medial and lateral epicondylitis treatment and to compare the results.Materials and Methods: A total of 116 patients diagnosed with medial and lateral epicondylitis were included in the study. The patients were divided into ESWT group and control group. The patients in the control group received a total of 15 sessions of conventional physical therapy (Hotpack, Transcutaneous electrical nerve stimulation (TENS)) once a day for 30 minutes.Whereas, ESWT was applied to the patients in the ESWT group as 2 sessions per week, for a total of 6 sessions. Pain severity of the patients was measured with Visual Pain Scale (VAS), grip strength with a hand dynamometer and functional level with the Patient Based Forearm Assessment Questionnaire (PFEQ).Measurements were made in all groups before treatment, after treatment and 1 month after treatment.Results: In comparisons between groups, there was a significant decrease in VAS and PFEQ values after treatment compared to the control group in the ESWT group (p
Keywords: Epicondylitis; functionality; pain; shock wave therapy